HUBUNGAN RESPON TIME PERAWAT DENGAN KEPUASAN PASIEN DI INSTALASI RAWAT JALAN RSUD BUDHI ASIH - Lutfi Riskyta Istikomah (2022)
Response time is the time in receiving health services when the patient registers until he arrives at the polyclinic and is checked by the nurse quickly and accurately. Response time can affect patient satisfaction based on the fulfillment of health services. This study aims to determine The Relationship of Nurse Response Time to Patients in the Outpatient Installation of Budhi Asih Hospital. The research design used descriptive analytic design with cross sectional method. The sampling technique in this study used accidental sampling with 170 respondents as a sample of patients in outpatient installations, namely internal medicine, surgery and pulmonary polyclinics. The instruments used are questionnaires and nurse response time observation sheets and patient satisfaction questionnaires. Response Time of nurses as many as 92 respondents (54.1%) "fast" that is ≤60 minutes and satisfaction level of 101 respondents (59.4%) "satisfied". The Chi-Square results obtained pValue 0.000<0.05, this indicates a relationship between nurse response time and patient satisfaction in the outpatient installation of Budhi Asih Hospital. It is expected that there will be additional nurse human resources so that it can increase the nurse's response time in carrying out nursing care and patient satisfaction will be even better with the health services obtained.